Organizational change : - Cawsey, T. F. (SAGE, 2016)
This unique toolkit provides insights and practical tools for anyone involved in organizational change. Bridging current theory with practical applications, this book combines conceptual models with concrete examples and useful exercises to dramatically improve the knowledge, skills, and abilities of students in creating effective change.